Climatic evolution in the Australian region over the last 94 ka - spanning human occupancy -, and unveiling the Last Glacial Maximum. (1st December 2020) - De Deckker, P.; Moros, M.; Perner, K.; Blanz, T.; Wacker, L.; Schneider, R.; Barrows, T.T.; O'Loingsigh, T.; Jansen, E.
Abstract: The Quaternary is well known for being a period of the geological record that saw significant and alternating climatic fluctuations. Here, we concentrate on the last 94 millennia that saw Australia and its surrounding seas undergo significant environmental changes. Importantly also it is during that this period of time includes the arrival and settlement of humans in Australia. Following on from Marine Isotopic Stage 4 (MIS4) that saw, over the period of 71-59 ka BP, a significant eustatic sea level drop (∼100 m), low sea-surface temperatures as well as glacial conditions on land, Australia experienced wet conditions again, but eventually progressively entered into a glacial phase. By then, humans had arrived on this large continent and later the megafauna progressively became extinct. This paper describes in detail the climate over this period, based principally on the high-resolution record of two marine sediment cores located offshore of the southern Australian margin, and that are then compared with known events on land as well as other deep-sea cores. Particular emphasis is placed on the period that spans the Last Glacial Maximum (LGM), the extent of which thus far had been poorly defined in the Australian region. Emphasis is placed on the period from 34 to 14 ka to demonstrate that (1) the LGM, defined here as the period 24 to 18 ka, was not always extremely dry and cold, and (2) that people were able to live in inland Australia as water existed in places, despite generally cold conditions. We also show using a series of ten maps - at 2 ka intervals over the 34-14 ka period - the waxing and waning of oceanic fronts such as the Subtropical and Subantarctic Fronts, link sea-surface temperatures (SST) with periods of glacial expansion in the Australian Alps and Tasmania, as well as the South Island of New Zealand, and the extent of the Leeuwin Current down to south of Australia. Aeolian dust was transported at sea over the main core site from ∼26 to 18 ka period, pointing to arid conditions in Australia, but this period was punctuated by two significant reductions in dust transport to both core sites, coinciding with a retreat of the Subantarctic Front away from the Australian southern coastline, and slight SST shifts for a few centuries at ∼24 and 22-21 ka BP. At the peak of the cold phase, from 23 to 18.4 ka, summer SST were of the order of 9 °C below that experienced during the middle of the Holocene at about 6 ka BP. A similar temperature drop was also experienced offshore the northwestern corner of Western Australia. Periglacial activity dates for the Australian mainland and Tasmania pool around ∼22 ka. On either side of the 24 ka event, the chain of lakes in the Willandra Lakes retained water and human activity was registered in the area. Elsewhere in Australia, water was present to sustain human populations during the cold and dry times. It is postulated here that northern Australia was at times quite wet, especially during MIS4. The cessation of the LGM is set on 18.4 ka from offshore southern Australia as confirmed for the deep-sea cores by several proxies, and more likely at 18 ka inland. Finally, we document that it took two millennia for "glacial" conditions to end in the Australian region as registered in our deep-sea core records, well after the lowest global sea level ∼20.6 and 20 ka, respectively, started to rise. There is also evidence of another very cold period determined on the Australian mainland, Tasmania and the South Island of New Zealand centred around 27 ka, after which time warmer conditions occurred before the start of the LGM. This is matched with our deep-sea records with very cold conditions and changes in oceanographic conditions. Highlights: 2 deep-sea cores provide information on the waxing and waning of oceanic fronts south of Australia. The Last Glacial Maximum for the Australian region spans 24-18 ka. 10 maps detail conditions in the Australian region spaning the period 34–14 ka. Environmental conditions for MIS2 & MIS4 are compared in great detail in the cores. Australia was arid and cold during the LGM but there was water to support human occupation.